2008
DOI: 10.1021/nl080745j
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Boron Nitride Nanoribbons with Tunable Electronic Properties

Abstract: We present theoretical evidence, based on total-energy first-principles calculations, of the existence of spin-polarized states well localized at and extended along the edges of bare zigzag boron nitride nanoribbons.Our calculations predict that all the magnetic configurations studied in this work are thermally accessible at room temperature and present an energy gap. In particular, we show that the high spin state, with a magnetic moment of 1 µ B at each edge atom, presents a rich spectrum of electronic behav… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
294
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 331 publications
(317 citation statements)
references
References 32 publications
20
294
2
1
Order By: Relevance
“…Metallicity of heteroatomic zigzag nanoribbons has been investigated theoretically in recent years [25][26][27] , and it has been pointed out that such 1D metallic channels can undergo magnetic transitions and eventually become half-metallic. However, no connection with the intrinsic polarization of the parent materials and with the existence of finite electric fields 28 has been drawn yet.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metallicity of heteroatomic zigzag nanoribbons has been investigated theoretically in recent years [25][26][27] , and it has been pointed out that such 1D metallic channels can undergo magnetic transitions and eventually become half-metallic. However, no connection with the intrinsic polarization of the parent materials and with the existence of finite electric fields 28 has been drawn yet.…”
Section: Resultsmentioning
confidence: 99%
“…This happens for heteroatomic honeycomb crystals such as BN and its functionalized derivatives, and for transition metal dichalcogenides, such as molybdenum disulfide. The existence of a polar discontinuity at the edges elucidates why metallicity can arise in honeycomb nanoribbons [25][26][27] or at inversion domain boundaries 36 . Second, we show that covalent atomic functionalizations, for example, with hydrogen or fluorine, can change the bulk polarization of a honeycomb lattice.…”
Section: Discussionmentioning
confidence: 99%
“…Zigzag edges exemplify the importance of edge effects in honeycomb lattices. [26,49] Zigzag nanoribbons are expected to present a spin-polarized ground state characterized by an antiferromagnetic spin arrangement (AFM) with opposite spins at each edge. [50] The high spin state solution, with all spins ferromagnetically aligned (FM), is higher in energy than the AFM state by 10 meV/edge atom for a 1.8 nm wide ribbon.…”
Section: Zigzag Nanoribbonsmentioning
confidence: 99%
“…Thus, instead of being a semimetal, BN honeycomb structure is a wide band-gap insulator with an energy gap of 4.64 eV. Soon after its synthesis, several studies on nanosheets 28 and nanoribbons [29][30][31][32] of BN have been reported.…”
Section: Introductionmentioning
confidence: 99%